Professional development in classroom assessment: a systematic literature review - Sanusi, Najdah; Zulkifli, Hafizhah; Hamzah, Mohd Isa; Jait, Kharhan (Intelektual Pustaka Media Utama, 2025)
Professional development in classroom assessment techniques plays a crucial role in enhancing student learning outcomes. The preferred reporting items for systematic review and meta-analysis (PRISMA)-guided systematic review of the research literature assesses these programs to identify effective methodologies, research limitations, and trends in development, providing evidence-based recommendations for education leaders and policymakers. A structured search of Scopus and Web of Science databases, using keywords “classroom,” “professional development,” and “assessment,” yielded a final set of 43 studies. The analysis revealed four major themes: i) student-centered education; ii) classroom practices and teacher development; iii) specialized education and teacher training; and iv) assessment in education. The review demonstrates the impact of professional development programs (PDP) on teachers and addresses challenges in improving student achievement. By adhering to recognized standards for systematic reviews, this study provides a comprehensive analysis of professional development in classroom assessment, highlighting various strategies, obstacles, and successes. The findings emphasize the significance of efficient assessment for student learning outcomes and offer insights into enhancing PDP in this critical area of education.